Synthesis, Computational Pharmacokinetics Report, Conceptual DFT-Based Calculations and Anti-Acetylcholinesterase Activity of Hydroxyapatite Nanoparticles Derived From Acorus Calamus Plant Extract - Pradeep, Sushma; Jain, Anisha S.; Dharmashekara, Chandan; Prasad, Shashanka K.; Akshatha, Nagaraju; Pruthvish, R.; Amachawadi, Raghavendra G; Srinivasa, Chandrashekar; Syed, Asad; Elgorban, Abdallah M.; Al Kheraif, Abdulaziz A.; Ortega-Castro, Joaquín; et al. (Frontiers in Chemistry, 2021)
Over the years, Alzheimer’s disease (AD) treatments have been a major focus, culminating in the identification of promising therapeutic targets. An herbal therapy approach has been required by the demand of AD stage-dependent optimal settings. Present study describes the evaluation of anti-acetylcholinesterase (AChE) activity of Hydroxyapatite nanoparticles derived from an Acorus calamus rhizome extract (AC-HAp NPs). The structure and morphology of as-prepared (AC-HAp NPs) was confirmed using powder X-ray diffractometer (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and high-resolution transmission electron microscopy (HR-TEM). The crystalline nature of as-prepared (AC-HAp NPs) was evident from XRD pattern. The SEM analysis suggested the spherical nature of the synthesized material with an average diameter between 30 and 50 nm. Further, the TEM and HR-TEM images revealed the shape and size of as-prepared (AC-HAp NPs). The interplanar distance between two lattice fringes was found to be 0.342 nm, which further supported the crystalline nature of the material synthesized. The anti-acetylcholinesterase activity of AC-HAp NPs was greater as compared to that of pure HAp NPs. The mechanistic evaluation of such an activity carried out using in silico studies suggested that the anti-acetylcholinesterase activity of phytoconstituents derived from Acorus calamus rhizome extract was mediated by BNDF, APOE4, PKC-γ, BACE1 and γ-secretase proteins. The global and local descriptors, which are the underpinnings of Conceptual Density Functional Theory (CDFT), have been predicted through the MN12SX/Def2TZVP/H2O model chemistry hoping that they could be of help in the comprehension of the chemical reactivity properties of the five ligands considered in this study. With the further objective of analyzing their bioactivity, the CDFT studies are complemented with the estimation of some useful computed pharmacokinetics indices , their predicted biological targets, and the ADMET parameters related to the bioavailability of the five ligands are also reported.